2013
DOI: 10.3109/13693786.2013.777858
|View full text |Cite
|
Sign up to set email alerts
|

Species ofCandidaas a component of the nasal microbiota of healthy horses

Abstract: Respiratory infections are a common problem among equines and occur with variable rates of morbidity and mortality. Although some fungal species are considered primary agents of respiratory tract infections in several mammals, their relevance in respiratory diseases of equines is frequently neglected. In the present study, we performed an active search for Candida spp. in the nasal cavity of horses. The presence of Candida spp. was investigated through the use of nasal swabs that were streaked on culture media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
2
14
1
1
Order By: Relevance
“…recovered from other healthy animals [6,[8][9][10][11]. Resistance to azoles was observed in C. tropicalis and C. albicans strains, corroborating previous observation of resistance in Candida spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…recovered from other healthy animals [6,[8][9][10][11]. Resistance to azoles was observed in C. tropicalis and C. albicans strains, corroborating previous observation of resistance in Candida spp.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have shown high rates of azole resistance in Candida spp. from animals, such as dogs [6], birds [7,8], prawns [9] and horses [10]. However, there are no reports on the antifungal susceptibility of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…The results found in this study are in clear contrast with those of previous reports that reveal alarmingly high rates of azole resistance among Candida strains of veterinary origin (6)(7)(8)(9)(10)(11)(12)(13). Notably, 47.8% of our isolates were collected between 2008 and 2014, when the first reports of substantial prevalence of azole resistance among yeast isolates obtained from animals were being published.…”
contrasting
confidence: 56%
“…The results of some recent studies of yeast collections of animal origin suggest that azole resistance is also relatively common among isolates from diverse host species and that even healthy individuals can serve as a reservoir of resistant strains (6)(7)(8)(9)(10)(11)(12)(13). For example, Cordeiro et al (10) found resistance rates of Ͼ45% for fluconazole and itraconazole, and a 37.5% rate of cross-resistance to both compounds, in a Brazilian collection of 64 Candida tropicalis isolates obtained from several animal species.…”
mentioning
confidence: 99%
“…When the internal and external environments of the host change, the density and quantity of the aforementioned resident microbes decrease, whereas a large number of pathogenic agents (Haemophilus influenzae, Streptococcus pneumoniae, influenza virus, respiratory syncytial virus, coronavirus and Aspergillus spp., etc.) propagate and adhere to epithelial surface receptors, thus initiating a plethora of immune reactions that eventually lead to the occurrence of diseases (16).…”
Section: Respiratory Tract Microecology Under Abnormal Circumstances mentioning
confidence: 99%